Elastic Properties of Fullerites and Diamond‐Like Phases. Issue 1 (7th December 2018) - Rysaeva, Leysan Kh.; Baimova, Julia A.; Lisovenko, Dmitry S.; Gorodtsov, Valentin A.; Dmitriev, Sergey V.
Abstract : Diamond‐like structures, that include sp 2 and sp 3 hybridized carbon atoms, are of considerable interest nowadays. In the present work, various carbon auxetic structures are studied by the combination of molecular dynamics (MD) and analytical approach. Two fullerites based on the fullerene C60 and fullerene‐like molecule C48 are investigated as well as diamond‐like structures based on other fullerene‐like molecules (called fulleranes), carbon nanotubes (called tubulanes) and graphene sheets. MD is used to find the equilibrium states of the structures and calculate compliance and stiffness coefficients for stable configurations. Analytical methods are used to calculate the engineering elastic coefficients (Young's modulus, Poisson's ratio, shear modulus and bulk modulus), and to study their transformation under rotation of the coordinate system. All the considered structures are partial auxetics with the negative value of Poisson's ratio for properly chosen tensile directions. It is shown that some of these structures, in a particular tension direction, have a very high Young's modulus, that is, 1852 GPa for tubulane TA6. Abstract : Elastic constants of auxetic diamond‐like phases are fully analyzed including calculation of Poisson's ratio, Young's modulus, shear and bulk modulus. The variation of Poisson's ratio and Young's modulus upon coordinate system rotation is analyzed with the help of analytical calculations.